Trabalho social com famílias: uma demanda para a formação profissional em Serviço Social - Silva, Henrique Manoel Carvalho (2018)
This work discusses the professional training process of the Social Worker and relate it to its practice in everyday life with the families attended in their workspaces. It focuses on the studies and analyses of a specific subject, related to the “families” thematic. Taking as an observation post survey conducted on the menus and curricular grids of Social service courses in the face-to-face mode, recognized by the Ministry of Education (MEC) and in activity, of the 5 (five) regions of Brazil. This reflection also emphasize the need for a more enlarged and decisive participation of the professionals when in practice, with the theoretical basis of the knowledge acquired in the professional training process